Artificial intelligence in teaching social disciplines: Opportunities and challenges of tools - Alla Lobanova; Iryna Hrabovets; Olena Prykhodko; Valerii Karytka; Liudmyla Kalashnikova; Liudmyla Chernous (Academy of Cognitive and Natural Sciences, 2024)
Based on the analysis of scientific sources and practical experience in teaching social disciplines, the article reveals the role and problems of using AI in the system of higher education. The scientific opinion about the inevitability of using AI, despite its risks, in teaching social disciplines is expressed. A comparative analysis of the subject area, conceptual apparatus, functional purpose and research methods of social disciplines is carried out. Similar features are revealed, the basis of which is their focus on the scientific study of the social and psychological behaviour of individuals, social groups and communities. On the example of didactic methods of teaching social disciplines in higher education, the expediency of using AI tools in the process of teaching is substantiated. Their main capabilities are personalised learning, forecasting and trend analysis, data visualisation, simulations and virtual laboratories, speech, video and voice interfaces, assessment tools, and generation of comments and feedback. Clarification of the principles and main possibilities of using AI tools has revealed the main problems, which include ethics, reliability, transparency, insufficient professional training of teachers and imperfect legal support. We outline prospects for further research on the peculiarities of using AI tools to teach social disciplines in higher education.